Ética e moral na formação inicial de professores - Amorim Neto , Roque do Carmo (2008)
The purpose of this paper was to analyze the implications of the ethics conception and moral in the teachers' initial formation, through the National Curricular Guidelines of the Pedagogy course, promulgated in the year of 2006, based on Lawrence Kohlberg's Moral Development theory. We have started with the following research problem: the sense of ethics and moral in the National Curricular Guidelines of the Pedagogy course. A qualitative research has been accomplished in order to reach the purpose of this paper, which interpreted the explicit or implicit meanings of the foregoing legislation leading to the assumption of an hermeneutical approach, without the intention to search for either some truth or specific information of the text but the construction of senses, starting from inferences. Besides presenting in details the theory of Lawrence Kohlberg's Moral Development, the research report also presents a brief historical vision of the educators' formation in Brazil, from the creation of the Pedagogy course to the promulgation of its National Curricular Guidelines. The results of the research showed the following aspects: a) inappropriate substitution of the “moral” term for the “ethics” term, which implicates the extinction of the “moral” word as the impoverishment of the “ethics” word, which loses its finalistic dimension as a search for a happy life; b) the educator's role as facilitator of the human development in their different contents; c) the expectation of the analyzed legislation that the attendees of the Pedagogy course possess the highest levels of moral development, although it doesn't point the means to achieve it; d) the importance, in the educational formation, of practices which enable a self encounter, such as own biographical writing present in the “Patchwork quilt” and even the psychotherapeutic practice as possibility of appropriate existence of the affectivity. Finally, the text emphasizes the necessary space to the Spirituality in the educational formation, which integrates and overcomes the dichotomy among Spirituality while horizontal transcendence ruled by relationships of “unconditional hospitality”, “care”, “justice”. Spirituality while vertical transcendence, as expression of religiosity, essential aspects for teachers' initial formation, whose purpose is to favor their students' human development.